Design, development and manufacturability study of aerospace actuator motor - Tom, Liya (2024)
Climate change concerns and its impact on the environment have prompted the aviation industry to explore more electric and hybrid aircraft solutions, given that the aerospace sector contributes approximately 2% of global CO2 emissions. After conducting a comprehensive study of the three primary areas of electrification which includes, propulsion, power generation, and actuation, it was determined that this thesis would primarily focus on actuation due to the allocated timeframe and cost constraints.